Practice-driven research on enterprise transformation third working conference, PRET 2011, Luxembourg-Kirchberg, Luxembourg, September 6, 2011: proceedings - PRET 2011 (2011 Kirchberg, Luxembourg); Harmsen, Frank (Berlin, Heidelberg Springer, 2011)
This volume constitutes the proceedings of the Third Working Conference on Practice-Driven Research on Enterprise Transformation (PRET), held in Luxembourg, on September 6, 2011, as the industrial track of the 13th IEEE Conference on Commerce and Enterprise Computing (CEC 2011). The third edition of PRET marked a close collaboration between academia and practice. With the specific purpose of mutual learning and cross fertilization, top practitioners from industry were invited to submit case studies. To give them enough space for presentation, only four academic papers were accepted. These papers were submitted with a length of 25 pages to enable a more detailed coverage of the related research and to stimulate further discussions during the conference. The topics covered are enterprise architecture, business and IT alignment, and business process management and evaluation.
Keywords: Management information systems -- Congresses; Electronic books